Effect of MWCNT particles on wear loss in dry sliding wear of PEEK matrix composites. (2019) - Kumar, D.; Rajmohan, T.
Abstract: In present circumstances nano particles reinforced with polymer matrix composites (PMC) are used for plentiful applications. Poly-ether-ether-ketone (PEEK) is enactment thermoplastic which have been used extensively in many engineering applications due their excellent mechanical, thermal electrical properties and wears resistance. Multi Wall Carbon Nano Tubes (MWCNT) reinforced PMCs can improve the properties of matrix material in terms of frictional resistance and tensile strength. In the current research, the wear performance of MWCNT reinforced PEEK matrix composites is examined using the pin-on-disk apparatus under dry condition. The wear parameters such as load, sliding speeds, temperature and wt % MWCNT are considered to evaluate wear loss in the composites. The MWCNT reinforced PEEK matrix composites were prepared by using melt mixing technique. Machining and polishing operations were used to make the pin size of square 8 mm and height 30 mm. Response surface design is engaged to perform the experiments. After wear test the worn out surfaces are studied through scanning electron microscopy.